The Simultaneity of Strategic Financial Decisions: Evidence from PSX listed Firms - Maqbool, Asifa; Nazeer, Nadia; Nawaz, Dil; Maqbool, Anum (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigates the interrelationships among financing, dividends, and the investment choices of non-financial firms listed on PSX. Unlike previous research, which primarily focused on developed nations with well-developed financial markets and investor protection laws, this study examines businesses in a developing economy characterized by fragile corporate governance, precarious investor protection laws, and political instability. The aim of this study is to shed light on the unique decision-making processes of managers operating in such contexts. This study employs a framework of simultaneous equations considering the flow of funds identity and utilizes the 3SLS estimation technique, which addresses the limitations of single-equation estimation methods. The findings reveal significant interdependencies among corporate financing, dividends, and investment decisions. Financing decisions positively influence dividend decisions and vice versa. Similarly, financing decisions positively impact investment decisions and vice versa. Moreover, dividends and corporate investments have been shown to be competing uses of funds. The results highlight the sensitivity of all three financial decisions to internal cash flows. Additionally, leverage and internally generated cash flows are identified as alternative sources of funds, while investment and dividend decisions are constrained by both internal funds and external debt. These findings align with the flow of funds approach and provide valuable insights for corporate managers and investors to understand the dynamics of financial choices in non-financial firms. This study contributes to the literature by filling a gap in knowledge regarding the interactions among financing, dividends, and investment decisions in emerging markets.